Acute Kidney Injury Is Associated With In-hospital Mortality in Older Patients With COVID-19. (16th July 2020) - Yan, Qi; Zuo, Peiyuan; Cheng, Ling; Li, Yuanyuan; Song, Kaixin; Chen, Yuting; Dai, Yue; Yang, Yi; Zhou, Lun; Yu, Weiwei; Li, Yongsheng; Xie, Min; et al.
Abstract: Background: The epidemic of COVID-19 presents a special threat to older adults. However, information on kidney damage in older patients with COVID-19 is limited. Acute kidney injury (AKI) is common in hospitalized adults and associated with poor prognosis. We sought to explore the association between AKI and mortality in older patients with COVID-19. Methods: We conducted a retrospective, observational cohort study in a large tertiary care university hospital in Wuhan, China. All consecutive inpatients older than 65 years with COVID-19 were enrolled in this cohort. Demographic data, laboratory values, comorbidities, treatments, and clinical outcomes were all collected. Data were compared between patients with AKI and without AKI. The association between AKI and mortality was analyzed. Results: Of 1764 in-hospital patients, 882 older adult cases were included in this cohort. The median age was 71 years (interquartile range: 68–77), 440 (49.9%) were men. The most presented comorbidity was cardiovascular diseases (58.2%), followed by diabetes (31.4%). Of 882 older patients, 115 (13%) developed AKI and 128 (14.5%) died. Patients with AKI had higher mortality than those without AKI (68 [59.1%] vs 60 [7.8%]; p  < .001). Multivariable Cox regression analysis showed that increasing odds of in-hospital mortality are associated with higher interleukin-6 on admission, myocardial injury, and AKI. Conclusions: Acute kidney injury is not an uncommon complication in older patients with COVID-19 but is associated with a high risk of death. Physicians should be aware of the risk of AKI in older patients with COVID-19.